1994
DOI: 10.1007/bf02368248
|View full text |Cite
|
Sign up to set email alerts
|

A device for subjecting vascular endothelial cells to both fluid shear stress and circumferential cyclic stretch

Abstract: The proposal of the role of mechanical forces as a localizing factor of atherosclerosis has led many researchers to investigate their effects on vascular endothelial cells. Most previous efforts have concentrated on either the fluid shear stress, which results from the flow of blood, or the circumferential "hoop" stretch, which results from the expansion of the artery during the cardiac cycle. In fact, arterial endothelial cells are subjected to both fluid shear stress and cyclic hoop stretch in vivo. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 9 publications
4
55
0
Order By: Relevance
“…Both of these mechanical stimuli influence vascular cell functionality. For example, if ECs are grown on a deformable substrate and subjected to cyclic uniaxial stretching, they reorient away from the stretching direction (Wang et al 2000;Owatverot et al 2005), and it is observed that the alignment of ECs subjected to WSS appears to be significantly enhanced by the addition of cyclic stretching (Moore Jr et al 1994). In fact, Owatverot et al 2005 suggest that, in vivo, arterial ECs are likely to be receiving a stronger cyclic stretch stimulus than WSS stimulus.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both of these mechanical stimuli influence vascular cell functionality. For example, if ECs are grown on a deformable substrate and subjected to cyclic uniaxial stretching, they reorient away from the stretching direction (Wang et al 2000;Owatverot et al 2005), and it is observed that the alignment of ECs subjected to WSS appears to be significantly enhanced by the addition of cyclic stretching (Moore Jr et al 1994). In fact, Owatverot et al 2005 suggest that, in vivo, arterial ECs are likely to be receiving a stronger cyclic stretch stimulus than WSS stimulus.…”
Section: Discussionmentioning
confidence: 93%
“…In monolayers, cells align perpendicular to the direction of cyclic stretching whereas within three-dimensional environments, cells align in the direction of cyclic stretch (Rubbens et al 2009). For instance, ECs align with the mean direction of flow and perpendicular to the direction of cyclic stretching (Moore Jr et al 1994). SMCs align in the direction of (circumferential) cyclic stretching, and it is observed that in 2D monolayers they align perpendicular to the applied haemodynamic WSS (Lee et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…We will refer to the phase angle between CS and WSS as the stress phase angle (SPA). Several groups have examined morphological and biochemical responses of ECs simultaneously subjected to WSS and CS which were in phase (SPA = 0°) and have observed that the response to simultaneous forces differs from the response to the individual forces [13, 18, 19], but the effects on EC behavior of simultaneous WSS and CS at physiological SPA has not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…On the venous side of the systemic circulation, there is almost no diameter variation due to the low pressure pulse. It is also well known that strain affects EC morphology [11, 12, 13]and biochemical response [14, 15, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…3 Thus, the behavior of vascular cells such as ECs and SMCs cultured on stretchable substrates which were periodically stretched and relaxed is of interest and was analyzed by various investigators. 23,25,33,36,38,42,43,52,53 These studies have shown that vascular cells tend to align perpendicular to the direction of strain independently of their animal or tissue origin. This suggests that, irrespective of cellular species and tissue and irrespective of the usage of primary cells or non-vascular cell lines, mechanical stressinduced cellular alignment is a common behavior of adhesive cells in vitro, which may operate to induce cellular orientation in tissues in vivo.…”
Section: Discussionmentioning
confidence: 99%